1986
DOI: 10.1042/bj2370713
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of cis-platinum (cis-diamminedichloroplatinum) on regulation of liver and kidney haem and haemoprotein metabolism. Possible involvement of γ-glutamyl-cycle enzymes

Abstract: The treatment of rats with cis-platinum (cis-diamminedichloroplatinum) for 1, 3 or 7 days elicited vastly different responses in the liver and the kidney in activities of enzymes of haem-metabolism pathway and gamma-glutamyl-cycle enzymes. The differences resided in the magnitude, direction and the time course of responses. In general, the liver was by far less severely affected, and when a response was elicited, it displayed an earlier onset (1-3 days), with a return to normal at 7 days. In the kidney, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Therefore, a decrease in the glutathione peroxidase activity could cause accumulation of H20 2 and lipid hydroperoxides, thus leading to deleterious effects. These results correlate well with those of Vernie et al [38] and Milano et al [39] who showed that cisplatin inhibited erythrocyte glutathione peroxidase, and with those re cently published by Hannemann and Baumann [40], Maines [30] did not reveal any effect of cisplatin treat ment on GSH content nor on glutathione reductase activ ity in the kidney. This discrepancy may be explained by the difference in the rat strains used and the treatment regimen (see above).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Therefore, a decrease in the glutathione peroxidase activity could cause accumulation of H20 2 and lipid hydroperoxides, thus leading to deleterious effects. These results correlate well with those of Vernie et al [38] and Milano et al [39] who showed that cisplatin inhibited erythrocyte glutathione peroxidase, and with those re cently published by Hannemann and Baumann [40], Maines [30] did not reveal any effect of cisplatin treat ment on GSH content nor on glutathione reductase activ ity in the kidney. This discrepancy may be explained by the difference in the rat strains used and the treatment regimen (see above).…”
Section: Discussionsupporting
confidence: 82%
“…They suggest that the mechanism of depletive action of cisplatin on microsomal cytochrome P-450 involves an impairment of the effective assembly of heme and apoprotein moieties. Maines [30] reported an increase in the kidney cyto chrome P-450 7 days after cisplatin treatment. This discrepancy may be explained by the difference in rat strains used and the treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin-cysteine-conjugates have been identified in the kidneys of cisplatin-treated rats (25). Maines incubated cysteine and cisplatin in a 2:1 molar ratio for 30 min at 37°C (59). He reported that in the kidney the cysteine-platinum incubation mixture was a more potent inhibitor of hemometabolism and glutathione synthesis than cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Bose and coworkers reported a kinetic analysis of the reaction of cisplatin with cysteine (Bose et al, 1997). Cysteine conjugates of cisplatin have been identified in the kidney (Maines, 1986).…”
Section: Downloaded Frommentioning
confidence: 99%